Embodying Abortion: Approaches to Sexual and Reproductive Experiences of the Cairene Youth. - Morales Cosano, Ruth (AUC Knowledge Fountain, 2023)
Whilst abortion in Egypt has been sorely neglected in academic literature, and highly criminalized by state institutions, women in Egypt have by no means ceased to perform it and, what is more, upon reasons that exceed any institutional or legal reasoning. The thesis stems from the need to give voice and continuity to the experiences of women who abort in Cairo. Given the almost complete lack of material showcasing this reality, this research project investigates the meaning-making process of abortion among Cairo's middle and upper classes. Understanding this construction requires studying abortion in its embeddedness in the material, social, and political context. Shaped by all social actors, this happening is ultimately operationalized in women’s bodies. Its meaning, which takes up form in a contested everydayness, is inherently linked to sexuality, and reproduction for they all engrain in the construction of the gender-based continuum. Abortion exists through the body in production and that is why this paper approaches gender embodiment from a time-mediated approach. Placing the focus on time and embodiment allows seeing abortion not as the moment of emergence in which a woman decides to interrupt pregnancy, but rather as a continuum of bodily experiences throughout the woman’s life. Understanding this bodily experience as a life process helps us dislocate the practice of abortion as concrete (concrete moments, concrete places, and concrete people), and relocate it to unimaginable sites of experience and practice.